Karen Glente, Karin Kryger og Orla Pedersen (red.): Dydens løn. Soldenfeldts Stiftelse 1894-1994. (Christian Ejlers' Forlag, 1994). 160 s., 200 kr. - Paludan-Müller, Ny (Historie/Jyske Samlinger, 1995)
-